Analysis of Marketing Communication Strategies in Increasing Sales Volume of Rini's Cake During the Covid-19 Pandemic - Hasanah, Uswatun; Nurulita, Vica Widiyana; Budiman, Arief; Kanita, Ghia Ghaida (Universitas Pendidikan Indonesia, 2021)
The Covid-19 pandemic occurred in Indonesia and all over the world, of course, it has an effect on daily activities carried out, from a normal atmosphere to a new atmosphere or new normal which of course requires all parties to adapt again in order to survive. This happened in Rini's Cake's MSME business marketing process, so a study was carried out aimed at restructuring the marketing communication strategy and looking for creative ideas to increase sales volume in the midst of the Covid-19 pandemic. This research is a qualitative exploratory research using purposive sampling method, the data collected consists of primary data and secondary were obtained from interviews, observations, reports sales and journals before. The results of this study are that Rini's Cake has a strategic design in increasing sales volume that has been adjusted to the Covid-19 pandemic so that the sales volume of Rini's Cake products can still go on and there is an increase and this research indirectly complements the previous research.